ASSESSMENT OF THE SOCIO-ECONOMIC BENEFITS OF WATER TRANSFER FROM THE GURARA DAM TO USUMA DAM, NIGERIA - wada, Arome Joseph; Iguisi, Edwin; Muhktar, Ibrahim (FUDMA JOURNAL OF SCIENCES, 2025)
The Lower Usuma Dam, commissioned in 1982, could not cope anymore with the water needs of Abuja’s spiraling population, whose daily demand for water was expected to hit the high mark of one million cubic meters in 2030, up from 210,000 cubic meters in 2002. The study examined the socio-economic benefits of inter-basin water transfer from the Gurara dam to Usuma dam in Nigeria. It examined the nature of the EIA’s predicted impacts of the project and compared with the actual social and economic impact of the project on the residents. Secondary data was obtained from the compendium of the Gurara transfer project by the Federal Ministry of Water Resources Abuja while primary data were acquired through questionnaire survey. Data were analyzed using descriptive and inferential statistics. The study simply conducted a monitoring and post auditing of the predicted socio-economic impacts of the inter-basin water transfer from Gurara to Usuma Dam project. Findings from the actual field survey revealed that among the eight socio-economic variables considered, only two has a significant mean which are educational Status .448 (1st) and Monthly Income .412 (2nd) which mean that there is a significant improvement in the educational qualification and monthly income level of residents in the study area as predicted, however, other variables such as occupational status .297, infrastructural development .226, health condition .201, indirect jobs .186, loss of farmland .182 and direct jobs .120 all returned a negative relationship.